Digitalisasi Manajemen Kewirausahaan Melalui Google Maps pada Usaha Donat dan Kue Bawang Fatir - Khoirunnisa Lubis; Romaito Batubara; Larasati; Diva Andre Syahreza; Ahmad Fauzi Pulungan; Siti Suaibah Lubis; Salwah; Amelia Dewita; Isti Rahma; Ayu Meita Puteri Siregar (Jurnal Ragam Pengabdian, 2025)
This community service program was carried out with the aim of strengthening entrepreneurial management capacity while supporting the digitalization process of the home-based business “Donat and Kue Bawang Fatir,” located in Roburan Lombang Village. The business has been operating for approximately ten years; however, throughout its development, it has faced several challenges, including limited promotion, declining consumer numbers, and a marketing reach that remains confined to the local area. To address these issues, the KKN 24 Roburan Lombang community service team designed several strategies, including mentoring in simple business management, training in measurable financial management, and the application of digital technology through the registration and optimization of the business profile on Google Maps. These efforts are expected to provide added value for the business, particularly in improving accessibility and visibility in the digital sphere. The results of the program indicate an increased understanding of digital literacy among business owners, greater convenience for consumers in locating the business, and an expansion of the market reach beyond the village. These findings affirm that digitalization through the use of Google Maps can serve as a strategic step in ensuring the sustainability and competitiveness of small rural businesses while also creating opportunities for more inclusive and sustainable local economic development.